Importance et évolution des investissements directs en Belgique - Christophe Piette (National Bank of Belgium, 2007)
– The aim of this study is to give an overview of recent developments in Belgium's direct investment relations with the rest of the world. The analysis is based mainly on two sets of statistics drawn up by the National Bank of Belgium, namely, data on direct investment flows from the balance of payments on the one hand, and the results of an annual survey on direct investment carried out among Belgian companies, on the other. Foreign direct investment (FDI) flows between Belgium and the rest of the world have, broadly speaking, followed relatively similar trends to FDI flows observed worldwide, but at the same time have shown some specific characteristics, such as the influence of a few sporadic operations involving large amounts and significant differences within the various components making up FDI inflows and outflows, the former consisting essentially of capital injections in companies and the latter mainly taking the form of intercompany loans. This particular structural pattern stems from the presence of the coordination centres in Belgium and the special tax status that these companies enjoy. Apart from those investment flows attributable to the coordination centres, a large part of the FDI inflows recorded in the balance of payments concern investment by multinationals in third countries, for which resident companies act as intermediaries. Still disregarding funds invested in the coordination centres, the total figures compiled on the basis of the annual survey show that foreign shareholdings in Belgian firms, as measured on the basis of their book value, have stabilized since 2002. Moreover, statistics for subsidiaries of foreign companies established in Belgium show that there is still a fairly high proportion of them active in relatively labour-intensive industrial sectors. As for Belgium's FDI, the results of the direct investment survey point to a gradual expansion in Belgian companies' activities abroad, which are developing at a faster pace than their domestic business. Both data on outstanding equity and those for subsidiaries abroad indicate that foreign direct investment by resident firms is largely concentrated in other developed countries with similar economic features to Belgium's. This would tend to suggest that the extent of straight business relocations to low-wage countries by Belgian firms via investments abroad remains relatively limited.
Keywords: F21; F23; 330; Foreign direct investments; Auslandsinvestition; Belgien